Prophylactic internal iliac artery ligation versus balloon occlusion for placenta accreta spectrum disorders: A retrospective cohort study. Issue 1 (29th June 2020) - Papillon‐Smith, Jessica; Hobson, Sebastian; Allen, Lisa; Kingdom, John; Windrim, Rory; Murji, Ally
Abstract: Objective: To compare surgical outcomes between women undergoing prophylactic internal iliac artery ligation or preoperative placement of balloon‐occlusive devices at cesarean hysterectomy for placenta accreta spectrum (PAS) disorders. Methods: A retrospective cohort study was conducted at a tertiary‐care referral center for PAS disorders in Ontario, Canada. Eligible electronic records were reviewed of women undergoing cesarean hysterectomy for PAS disorders between November 2012 and June 2018. Outcomes for the ligation and balloon groups were compared primarily on procedure‐related complications and secondarily on total procedure time, bleeding and transfusion metrics, and intraoperative and postoperative complications. Results: Of the 79 cases of cesarean hysterectomy, 47 underwent balloon placement and 32 underwent ligation. Baseline characteristics between the groups were similar except for more emergency procedures in the ligation group (37.5% vs 12.8%, P =0.014). The balloon‐related complication rate was 5/47 (10.6%), with no reported complications in the ligation group ( P =0.077). Procedural time was longer in the balloon group (353 ± 14 vs 227 ± 13 minutes, P <0.001). Estimated blood loss was similar (1874 ± 245 mL vs 1713 ± 181 mL, P =0.590). Conclusion: Women undergoing prophylactic placement of endovascular balloons at caesarean hysterectomy for PAS disorders had a 10.6% procedure‐related complication rate and increased total procedure time, with no decrease in blood loss compared to those undergoing surgical ligation. Abstract : There is no advantage of endovascular balloon occlusion over ligation of the internal iliac arteries to prevent hemorrhage at hysterectomy for placenta accreta spectrum disorders.